Sams teach yourself Visual InterDev 6 in 21 days - Van Hoozer, Michael (Sams, 1998)
In just 21 days, you'll have all the skills you need to get up and running efficiently with Visual InterDev 6. With this complete tutorial, you'll master the basics and then move on to the more advanced features and concepts. In the process, you will truly learn how to use Visual InterDev to design and build dynamic and interactive Web applications.